Assessment of the genotoxic potential of tetrachlorvinphos insecticide by cytokinesis-block micronucleus and sister chromatid exchange assays. (December 2021) - Cobanoglu, Hayal; Cayir, Akin
Tetrachlorvinphos is an organophosphate that is classified as a carcinogen in humans by several authorities. Due to very limited data regarding the genotoxic potential, we aimed to comprehensively investigate in vitro genotoxic potential of tetrachlorvinphos. We performed our study by applying the cytokinesis-block micronucleus cytome and sister chromatid exchange (SCE) assays to human peripheral blood lymphocytes. We evaluated micronucleus (MN) and SCE frequencies and cytokinesis-block proliferation index in both exposed and non-exposed lymphocytes. We also calculated the chromosomal instability level in response to exposure by combining the results of MN and SCE. We found that MN frequency did not increase with exposure to tetrachlorvinphos (0–50 µg/ml). In contrast, we observed that SCE frequencies significantly increased with exposure to ≥5 µg/ml tetrachlorvinphos. Furthermore, exposure to tetrachlorvinphos at concentrations of 50 µg/ml induced a significant increase in chromosomal instability level ( p < 0.05). Cytokinesis-block proliferation index level did not significantly decrease in response to tetrachlorvinphos exposure. Our findings reveal that tetrachlorvinphos resulted in different DNA damages that were measured by two assays. Furthermore, our findings suggested that exposure to tetrachlorvinphos increased chromosomal instability that is a hallmark of many malignancies. We conclude that although tetrachlorvinphos does not significantly increase the MN level, the significant increase of both SCE and CIN frequencies indicates the genotoxic potential of tetrachlorvinphos in human peripheral lymphocytes. Additionally, tetrachlorvinphos is not cytotoxic in the range of tested concentrations.